1994
DOI: 10.1111/j.1464-410x.1994.tb07522.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary continence after reconstruction of classical bladder exstrophy (73 cases)

Abstract: The outcome of bladder neck reconstruction was unpredictable. Achievement of a balance between intravesical pressure and outlet resistance was difficult and often required secondary endourethral procedures. Persistent incontinence after bladder neck reconstruction was related to insufficient outlet resistance, an abnormal bladder or a combination of the two. Repeated bladder neck reconstruction, bladder augmentation, bladder neck suspension and reconstruction combined with augmentation were performed. These op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Gender was the strongest predictor of continence in this series and ultimately was achieved in 94% of females and 69% of males after BNR alone, BNR with augmentation cystoplasty, or bladder neck closure. Mollard et al [22] reported continence with urethral voiding in 69% of 54 patients at the 1-to 17-year follow-up after BNR, with the authors' technique being performed for most patients.…”
Section: Staged Approach For Repair Of Bladder Exstrophymentioning
confidence: 94%
“…Gender was the strongest predictor of continence in this series and ultimately was achieved in 94% of females and 69% of males after BNR alone, BNR with augmentation cystoplasty, or bladder neck closure. Mollard et al [22] reported continence with urethral voiding in 69% of 54 patients at the 1-to 17-year follow-up after BNR, with the authors' technique being performed for most patients.…”
Section: Staged Approach For Repair Of Bladder Exstrophymentioning
confidence: 94%
“…The Young-Dees-Leadbetter bladder neck reconstruction is the established method to create increased bladder outlet resistance in the exstrophy/epispadias complex [2,3]. However, the procedure and its modifications [6,10,11] require the use of some of the base of the bladder, which may have a limited capacity. Hollowell et al suggested that the normal bladder usually associated with primary epispadias may be disturbed by this major reconstructive procedure [12].…”
Section: Methodsmentioning
confidence: 99%
“…collagen, Teflon or polydimethylsiloxane particles (MacroplastiqueTM, Uroplasty Inc), material the needle was lubricated with EZ gelTM (Uroplasty Inc). (MPQ) [6][7][8]. The endoscopic suburothelial insertion of material into the posterior urethral region represents a minimally invasive technique which is less likely to interfere with bladder wall structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Second male patient might achieve acceptable continence after epispadias repair and bladder neck reconstruction, which was also suggested by Baird et al 4 . In another series, long-term follow-up for urinary continence after reconstruction of classical bladder exstrophy indicated unpredictable outcome 2,5 .…”
Section: Discussionmentioning
confidence: 99%